Antidiabetic Potential of Methanol Extract of Flamboyant (Delonix regia) Flowers - Eriani, Kartini; Hasanah, Uswatun; Fitriana, Rizky; Sari, Widya; Yunita, Yunita; Azhar, Al (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2021)
Providing scientific evidences for the medicinal benefits and possible toxic effects of the flamboyant flowers (Delonix regia (Bojer ex Hook.) Raf.) are very important to implementing the medicinal plant in this modern era. This study aimed to investigate antidiabetic potential of methanol extract of flamboyant flowers using a completely random design. Twenty-four male rats were randomly divided into 6 treatment groups with 4 replications: healthy rats (normal control, P1), diabetic rats treated with flamboyant flower extract of 0 (negative control, P2), 100 (P3), 200 (P4), and 400 mg/kg BW (P5), and rats which were induced by 0.45 mg/kg BW of Glibenclamide (positive control, P6). Diabetic condition was achieved by a single injection of alloxan 150 mg/kg BW. Treatments were given once a day for 14 days. On day 0, 3 and 18 blood samples were withdrawn from rats’ orbital vein for glucose measurement. All rats were sacrificed for liver, gastrocnemius muscles and pancreatic tissues collection. The liver and gastrocnemius muscle were subjected for glycogen measurement whereas pancreatic tissues were processed for histological examinations. Data was analyzed by ANOVA and followed by Duncan test. The results showed that flamboyant flowers extracts significantly (p<0.05) reduced blood glucose as well as degeneration and necrosis of pancreatic β cells. Optimal dose to decrease blood glucose and pancreatic cell degeneration was 200 mg/kg BW; whereas optimum dose to decrease pancreatic cell necrosis was 400 mg/kg BW. In conclusion, flamboyant flower extract can reduce blood glucose in rats. This is the first that shows antidiabetic potential of local Flamboyant flower extracts along its toxicity effect to pancreatic tissues. These information could become a basic consideration for the use of the plant extracts as a candidate to cure patients with diabetic problems.